Market Orientation and Export Performance: A Ghanaian Study - Hinson, R.; Ofori, D.; Kastner, A.; Mohammed, M. (African Journal of Economic and Business Research 3(2&3): 62-90, 2007)
The paper investigates antecedents and environmental moderator effects on market orientation and export performance of Ghanaian firms. The results of our survey of 142 exporters show that market orientation relates positively to export performance for both subjective and objective measures used. Environmental moderators do not have any effect on market orientation and export performance for the firms under study. Antecedents to market orientation presented mixed whilst others were not. On the strength of the findings from this study, we posit that market-oriented firms compete more effectively and efficiently than their competitors.